(untitled) (Comparative Professional Pedagogy, 2024)
The article is devoted to the study of theoretical foundations for professional training of masters in music therapy in the USA. It is found that the intensive expansion of music therapists’ professional activity and the improvement of the scope of music therapy services put forward qualitatively new requirements for the personality of specialists of this profile and the system of their professional training in the USA. The analysis of scientific and pedagogical literature on the research problem, which highlights general issues of music therapy education, didactics of music therapy, application of competency-based, cultural, interdisciplinary, praxeological, ethical and deontological approaches, models of music therapists’ professional training, multicultural and experimental training, features of music therapists’ professional activities, reflective practices in music therapy, etc. is conducted. An active renewal of the theoretical basis of music therapy specialists’ professional training in the USA is revealed, primarily in accordance with current philosophical, psychological, pedagogical ideas and ideas about the essence and nature of human cognition. The integration of various learning theories, in particular behaviorist, connectivist, cognitive-constructivist, and social-constructivist, is substantiated and their use in the practice of training future masters in music therapy in the USA is presented. It is concluded that a rational synthesis of the ideas and provisions of these theories in the professional training of masters in music therapy in the US universities makes it possible to identify key factors and prerequisites for their successful acquisition of professional knowledge and experience. Therefore, it is possible to choose and implement the most constructive approaches to the organization of educational process. The prospects for further scientific studies regarding the substantiation of methodological approaches, which form the basis for professional training of masters in music therapy at the US universities, are determined.